AB1122 PREDICTION OF THE UTILITY OF ULTRASOUND EVALUATION IN RHEUMATOID ARTHRITIS BY THE CLINICAL FACTORS. (June 2019) - Asano, Takahiro; Suda, Masei; Rokutanda, Ryo; Yanaoka, Haruyuki; Fukui, Sho; Sawada, Haruki; Ikeda, Yukihiko; Koido, Ayako; Imai, Rui; Shimizu, Hisanori; Tamaki, Hiromichi; Tsuda, Tokutarou; et al.
Abstract : Background: It is known that ultrasound detects synovitis with higher sensitivity than physical examination in rheumatoid arthritis (RA), and the residual inflammation detected by ultrasound even in the patient achieving clinically remission well correlates with progression of erosion. 1 However, It is impossible to perform ultrasound evaluation on all the joints in all the patients in terms of time and human resource. Therefore, ultrasound use in RA should be more focused on situations when the physical findings and ultrasound findings likely to dissociate. Hirata et al showed the concordance between swelling or tenderness joint and ultrasound-detected synovitis are low in the PIP, MCP, and wrist joint. 2 Objectives: To investigate the factors that can predict dissociation between clinical and ultrasound-detected synovitis in the patient with rheumatoid arthritis. Methods: Patients aged 18 years or older who satisfied ACR/EULAR 2010 criteria who visited St. Luke's International Hospital from June 1, 2018 to November 9, 2018 and were performed ultrasound on PIP, MCP, and wrist joints were eligible for this study. We retrospectively reviewed the electronic medical chart and ultrasound data, and analyzed the dissociation of clinical synovitis defined as existence of swelling or tenderness and ultrasound-detected synovitis defined as both of power doppler grade and gray scale grade ≧1 or gray scale grade ≧2. Clinical evaluation was done by the attending physician who ordered the ultrasound evaluation. Ultrasound evaluation was done using standard scan technic 3 by the sonographers who are blinded to the clinical evaluation. The correlation between patient's characteristics and dissociation was analyzed using χ 2 test, Mann-Whitney U test and logistic regression analysis. Results: 51 joints in 32 patients (4 males, 28 females) were included in the study. Among the 32 patients, 18 was classified in the dissociation group (DG) and 14 in the non-dissociated group (NDG). No significant difference was observed in the patient's characteristics of DG and NDG. In the univariate analysis, the absence of swelling in the target joint had tendency to be the risk of dissociation. The same tendency was preserved in the multivariate analysis with the presence of tenderness in the target joint assigned as a covariate (OR 3.68, 95% CI = 0.85 - 15.90, p = .08). Conclusion: There was a numerical tendency that no swelling on the joint is a risk factor for the dissociation between clinical synovitis and ultrasound-detected synovitis. Future study with increased number of participants may identify more sensitive risk factors for dissociation, and enable to make an effective indication of ultrasound evaluation in the care of RA. References: [1] Kawashiri S, et al. Rheumatology 53.3, 2013: 562-569. [2] Hirata A, et al. Arthritis Care & Research Vol. 69, No. 6, June 2017: 801–806 [3] Naredo E, et al. Annals of the rheumatic diseases 64.3, 2005: 375-381. Disclosure of Interests: Takahiro Asano: None declared, Masei Suda: None declared, Ryo Rokutanda: None declared, Haruyuki Yanaoka: None declared, Sho Fukui: None declared, Haruki Sawada: None declared, Yukihiko Ikeda: None declared, Ayako Koido: None declared, Rui Imai: None declared, Hisanori Shimizu: None declared, Hiromichi Tamaki: None declared, Tokutarou Tsuda: None declared, Mitsumasa Kishimoto Consultant for: Kyowa Hakko Kirin Co., Ltd., Kenichi Yamaguchi: None declared, Masato Okada: None declared